2020
DOI: 10.1103/physrevb.102.094513
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectricity carried by proximity-induced odd-frequency pairing in ferromagnet/superconductor junctions

Abstract: We explore the role of proximity-induced odd-frequency pairing in the thermoelectricity of a ferromagnet when coupled to a conventional s-wave spin-singlet superconductor through a spin-active interface. By varying both the polarization and its direction in the ferromagnet and the interfacial spin-orbit interaction strength, we analyze the behavior of all proximity-induced pair amplitudes in the ferromagnet and their contributions to the thermoelectric coefficients. Based on our results for the Seebeck coeffic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 71 publications
(108 reference statements)
0
9
0
Order By: Relevance
“…In semiconducting AGNR junctions with Stone-Wales or 555-777 defects, we find thermodefect voltages as large as 1.45 mV K −1 and 1.7 mV K −1 , respectively, at room temperature. This can be compared to the conventional semiconducting [59] and ferromagnet-superconductor hybrid thermoelectric junctions [60][61][62] that usually produce voltages around sub-mV K −1 or μV K −1 , showing the impressive prospects of the present work for thermoelectric applications.…”
Section: Introductionmentioning
confidence: 95%
“…In semiconducting AGNR junctions with Stone-Wales or 555-777 defects, we find thermodefect voltages as large as 1.45 mV K −1 and 1.7 mV K −1 , respectively, at room temperature. This can be compared to the conventional semiconducting [59] and ferromagnet-superconductor hybrid thermoelectric junctions [60][61][62] that usually produce voltages around sub-mV K −1 or μV K −1 , showing the impressive prospects of the present work for thermoelectric applications.…”
Section: Introductionmentioning
confidence: 95%
“…In semiconducting AGNR junctions with Stone-Wales or 555-777 defects, we find thermodefect voltages as large as 1.45 mV/K and 1.7 mV/K, respectively, at room temperature. This can be compared to the conventional semiconducting [49] and ferromagnet-superconductor hybrid thermoelectric junctions [50][51][52] that usually produce voltages around sub-mV/K or µV/K, showing the impressive prospects of the present work for thermoelectric applications.…”
Section: Introductionmentioning
confidence: 96%
“…23 P. Dutta et al found that a ferromagnet/superconductor junction is an excellent TE system under certain conditions. 24 Y. Fujine et al investigated the magnetic and TE properties of a La 0.8 Sc 0.2 Co 1−z M z O 3 system and found that the Seebeck coefficient is strongly correlated with the behavior of magnetization. 25 All the above studies demonstrate that magnetism has a novel effect on the TE performance.…”
Section: Introductionmentioning
confidence: 99%